2017
DOI: 10.7554/elife.23845
|View full text |Cite
|
Sign up to set email alerts
|

Impaired respiration elicits SrrAB-dependent programmed cell lysis and biofilm formation in Staphylococcus aureus

Abstract: Biofilms are communities of microorganisms attached to a surface or each other. Biofilm-associated cells are the etiologic agents of recurrent Staphylococcus aureus infections. Infected human tissues are hypoxic or anoxic. S. aureus increases biofilm formation in response to hypoxia, but how this occurs is unknown. In the current study we report that oxygen influences biofilm formation in its capacity as a terminal electron acceptor for cellular respiration. Genetic, physiological, or chemical inhibition of re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
103
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 103 publications
(106 citation statements)
references
References 117 publications
1
103
2
Order By: Relevance
“…However, the mechanisms underlying the influence of oxygen upon biofilm formation have yet to be fully described. We recently reported that oxygen impacts S. aureus biofilm formation in its capacity as a terminal electron acceptor for cellular respiration (21). Decreased oxygen concentrations lead to diminished respiration, which serves as a signal that elicits programmed cell lysis (PCL), culminating in increased biofilm formation (21).…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…However, the mechanisms underlying the influence of oxygen upon biofilm formation have yet to be fully described. We recently reported that oxygen impacts S. aureus biofilm formation in its capacity as a terminal electron acceptor for cellular respiration (21). Decreased oxygen concentrations lead to diminished respiration, which serves as a signal that elicits programmed cell lysis (PCL), culminating in increased biofilm formation (21).…”
mentioning
confidence: 99%
“…We recently reported that oxygen impacts S. aureus biofilm formation in its capacity as a terminal electron acceptor for cellular respiration (21). Decreased oxygen concentrations lead to diminished respiration, which serves as a signal that elicits programmed cell lysis (PCL), culminating in increased biofilm formation (21). Chemical or physiological conditions that diminish respiration prompt increased biofilm formation.…”
mentioning
confidence: 99%
See 3 more Smart Citations